EVALUASI TINGKAT KEPUASAN MAHASISWA TERHADAP LAYANAN SISTEM INFORMASI AKADEMIK ATAU SIAKAD DALAM UNIVERSITAS TULUNGAGUNG - Af’fizatul Novita Anggraini Ningsih; Amilisa Kharisma; Nanda Silfiya Fatmawati; Linda Alfina Triani; Niken Agy Arimbi (Universitas Tulungagung, 2025)
The purpose of this study is to assess how satisfied Tulungagung University students arewith the services provided by the Academic Information System (SIAKAD). The evaluationwas conducted by analysing students' perceptions of system quality, information quality,and service quality provided by SIAKAD. In this study, a quantitative method was applied,in which data were obtained through the distribution of questionnaires to TulungagungUniversity students as the main source of information. The results showed that SIAKADprovides easy access to academic information for students, but there are still some obstaclessuch as access difficulties at certain times. In general, the level of student satisfaction withSIAKAD is in the satisfied category, but improvement is needed in service aspects anddevelopment of system features to increase user satisfaction in the future. This finding isexpected to be an input for the management of Tulungagung University in an effort todevelop a more interactive academic information system